(untitled) (Mongolian Journal of Humanities and Social Sciences, 2025)
The Mongolian folk heroic epic is a giant dinosaur of early oral poetry, a complex of multiple forms of the oral art tradition. Therefore, the Mongolian folk heroic epics have created many types of studies covering the wide scope of epic studies from ancient times until now. Herein, dozens of books and articles have been written and published, such as the study of character description of Mongolian heroic epics, the study of symbolism, the study of historical methodology, the biographical works of epic writers, and the rituals of epics. As far as we know our academics have compared and studied the hero of heroic epics from many aspects, nonetheless, there has not been any research that studies the hero as a god exclusively. Therefore, in this article, we have tried to compare the examples of some heroic epics as an exclusive study of the concept of "God in Mongolian heroic epics", which will raise issues such as how the concept of god exists in heroic epics, what kind of symbolism is appropriate, what logical meaning is attributed to it, and will the comparison contribute to another topic of research in the field of heroic epic studies. Нүүдэлчдийн туульс дахь Бурханы зарчмууд Монгол ардын баатарлаг туульс нь аман зохиолын аман уламжлалын олонх хэлбэрийн цогц, эрт үеийн аман яруу найргийн аварга том гүрвэл юм. Иймд эртнээс эдүгээг хүртэл монгол ардын баатарлаг тууль нь тууль судлалын өргөн цар хүрээг хамарч олон төрлийн судлалыг бий болгожээ. Үүнд монгол баатарлаг туульсын дүр дүрслэхүүний судлал, бэлгэдэл зүйн судлал, түүхэн арга зүйн судлал, туульчдын намтар уран бүтээл, туулийн зан үйл гэх мэт олон арван судлал судалгааны ном, өгүүллүүдийг бичиж хэвлүүлсэн байдаг. Манай эрдэмтэн судлаачид баатарлаг туульсын баатрыг олон талаас нь харьцуулан судалсан боловч бидний мэдэхээр баатрыг бурхан болох тухай дагнан судалсан судалгаа одоогоор хараахан гараагүй байна. Иймд энэ удаагийн өгүүлэлдээ “Монгол баатарлаг туульс дахь бурхны тухай” ойлголтыг дагнан судлах нь бурхан хэмээх ойлголт баатарлаг туульст хэрхэн оршиж буй, ямар бэлгэдэл зүйтэй болох, ямар учир зүйн утгад хамааруулдаг гэх мэт асуудлыг хөндөх, тууль судлалын хүрээнд ахин нэг сэдэвт судалгааг нэмэрлэх болов уу? хэмээн найдаж зарим нэг баатарлаг туульсын жишээн дээр харьцуулан судлахыг хичээсэн болно. Түлхүүр үг: Баатарлаг туульсын баатар, баатар, Бурхан, бурхан сахиус